Fall Armyworm, Spodoptera frugiperda (J.E. Smith) Management Strategies: A Synopsis - Khatri, S.; Tiwari, S.; Ghimire, D. (Journal of the Institute of Agriculture and Animal Science, 2020)
Fall armyworm (Spodoptera frugiperda) is a polyphagous pest with a host range, native to North and South America. This pest was formally reported for the first in January 2016 in Africa and in May 2018 in India. On 9 May 2019, this pest was first noticed in Nawalpur Nepal. 20-35% losses have been reported in maize crops. Since the outbreak of this pest from Africa, entomologists are working for their strategic management. This review aims to compile the fall armyworm (FAW) management works carried in the world and discuss their relevancy in Nepalese context. Of the various practices, chemical pesticides are one of the most commonly used tools followed by habitat management and other cultural practices. Insect pheromones are used for pest monitoring, and thereby to improve pest management decisions. Trap cropping, cover cropping, intercropping, maintaining floral diversity are some examples of habitat pest manipulation. Push-pull strategy uses Napier crop as a ‘Pull’ component and Desmodium crop as a ‘Push’ crop. These agro-ecological strategies change the behavior of FAW and able to trap or manage them in a certain area or certain crop, where pest can be managed manually or using other non-insecticidal strategies. This review work will be useful for the academicians, extension workers and plant protectionist to design a sustainable FAW management protocol.